2018
DOI: 10.1021/acs.orglett.7b03974
|View full text |Cite
|
Sign up to set email alerts
|

Flow Photochemistry as a Tool for the Total Synthesis of (+)-Epigalcatin

Abstract: The first total synthesis of (+)-epigalcatin was completed in a highly stereoselective manner starting from piperonal, 3,4-dimethylbenzaldehyde, and diethyl succinate. l-Prolinol was used as a chiral auxiliary. The crucial step in this procedure involves the construction of the cyclolignan framework by continuous-flow photocyclization of a chiral atropisomeric 1,2-bisbenzylidenesuccinate amide ester.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Melting points were determined on an Electrothermal, Model IA 9200 apparatus and are uncorrected. 1 H and 13 C NMR spectra were recorded on a Bruker AVANCE 500 spectrometer. Chemical shifts were reported in ppm from tetramethylsilane with the solvent resonance as the internal standard in CDCl3 solution.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Melting points were determined on an Electrothermal, Model IA 9200 apparatus and are uncorrected. 1 H and 13 C NMR spectra were recorded on a Bruker AVANCE 500 spectrometer. Chemical shifts were reported in ppm from tetramethylsilane with the solvent resonance as the internal standard in CDCl3 solution.…”
Section: Methodsmentioning
confidence: 99%
“…10 We found that L-prolinol is an excellent chiral auxiliary 11 and used for the formal synthesis of PPT 12 and the total synthesis of (+)-epigalcatin. 13 We also studied the regioselectivity in the photocyclization of cyclolignan precursors 14 and we used the bis-benzylidenesuccinyl platform as a photolabile protecting group for secondary amines. 15 Although the photocyclization of chiral bis-benzylidenesuccinates is relatively better studied, it is also possible to obtain cyclolignans via acid catalyzed cyclization, as shown in Charlton's total synthesis of (+)-lyoniresinol dimethyl ether, in which (-)-ephedrine was used as a chiral auxiliary and triflic acid (TfOH) as the catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was proven by further synthesis of another cyclolignan (+)-epigalcatin. 20 1R,2R-cis-podophyllic aldehyde, an important intermediate during the synthesis of (-)-podophyllotoxin, was converted to the first known heterodimer of podophyllotoxin and benzothiazole. This compound was much more active against the majority of the tested tumor cell lines than podophyllotoxin itself.…”
Section: Atropisomerism In Arylpyridine Derivativesmentioning
confidence: 99%
“…Czarnocki and coworkers reported in 2018 the total synthesis of (+)-epigalcatin using a photocyclization process under continuous flow UV irradiation conditions (Scheme 24) [85]. Diester 134 was condensed with aldehyde 120 at basic conditions, affording E , E -bisbenzylidenesuccinic acid 135 .…”
Section: Advances In the Synthesis Of Arylnaphthalene Derivativesmentioning
confidence: 99%